Tantangan dan Peran HR dalam Organisasi - Wiguna, Wahyu; Suharni, Suharni; Lela Widyanti; Burhannudin, Burhannudin (IPM2KPE, 2026)
This study aims to analyze the strategic role and challenges of Human Resource Development (HRD) in organizations, particularly in facing digital transformation and the dynamics of the modern work environment. The research method used was a qualitative approach using the Systematic Literature Review (SLR), which analyzed various national and international scientific literature for the 2020–2025 period through a process of selection, data reduction, thematic grouping, and data synthesis and interpretation. The results indicate that HRD plays a crucial role as a manager, developer, and driver of human resource quality through recruitment, training, competency development, increasing employee engagement, and establishing an adaptive and performance-oriented work culture. Furthermore, HRD also plays a role in integrating digital technology to improve the effectiveness of HR management. However, HR faces various challenges such as accelerated technological change, a skills gap, changes in digital and automated work methods, and the emergence of non-standard work models that raise ethical and regulatory issues. The conclusion of this study emphasizes that HRD must strategically transform by strengthening digital competencies, building flexible HR management systems, and integrating technological innovation to maintain the long-term sustainability of organizational performance. Keywords: Human Resource Development, Digital Transformation, Employee Performance